Integrated Marketing Communication Using Social Media in Promoting Embroidery Craft of Tasikmalaya - Susanti, Santi; Sukaesih; Gunawan, Wahyu (International Journal of Psychosocial Rehabilitation, 2019)
Embroidery is one of the handicraft products made by people in Tasikmalaya. Embroidery entrepreneurs in Tasikmalaya are divided into two categories: those who use traditional sewing machines that moved with feet and are known as kejek machines, as well as embroidery produced by computerized embroidery machines. The presence of computerized machines that were able to produce embroidery with more quantities did not eliminate the entrepreneurs who were still undergoing the embroidery business using traditional sewing machines. This study aims to reveal the construction of meaning for traditional embroidery entrepreneurs in maintaining their business among the entrepreneurs of computerized embroidery, as well as using the integrated marketing communication to promote their products to be accepted by their consumers. Using qualitative methods with a phenomenological approach, the results of the study show that the entrepreneurs interpreted their business as an effort to maintain the authenticity of the embroidery while maintaining the characteristics of Tasikmalaya as a city of crafts, especially embroidery. The IMC, which includes direct promotion and sales, public relations, and advertising, is carried out with social media, exhibitions, and collaborating with capital owners as fostered partners. The quality of the product is well maintained so that consumers remain loyal. With such IMC, traditional embroidery entrepreneurs can survive and develop until today.